Physics-Astronomy-Mathematics Sessions at SLA 2002: June 8-1: 2002 - Kizer Walker (Issues in Science and Technology Librarianship)
This article provides an overview of the sessions organized by SLA's Physics-Astronomy-Mathematics Division (SLA-PAM) at the Special Libraries Association's 93rd Annual Conference in Los Angeles.